A participação de crianças e familiares no cuidado em saúde mental : um grupo GAM no CAPSi de Vitória-ES - Gonçalves, Luana Gaigher (2018)
How can children participate in the care for their own mental health? How can those that historically are not seen as responsible or capable of answering for their own lives have the right to participate, voice opinions or express themselves? This work is part of a research situated in the field of child and adolescent mental health that seeks to problematize the low participation of children and their families in treatment, especially regarding the management of medication. In spite of the progress achieved in the process of the Brazilian Psychiatric Reform and the significant changes in the models of care and management in health practices, the matter of medication is still a sore point. The experiences of mental health service users and their relatives are rarely considered as part of the knowledge regarding treatment. And when these users are children, the problem becomes even more complex and challenging. In addition to the difficulties and barriers imposed by the production of mental disorder diagnoses, these children are also marked by a certain historical construction of childhood images, which on the one hand made it possible to protect children, but on the other, ended up generating impossibilities and putting limits on children’s participation in their care processes. Through the proposition of an Intervention Group (GI) with family members in the Center for Child and Youth Psychosocial Care (CAPSi), based on the strategy of the Autonomous Management of Medication (GAM), this research had as its guideline of work the deterioration of certain crystallized images of childhood. The hope of this work was to cultivate other possible relations with children — which involve other ways of thinking about and being with them — considering the exercise of participation an ethical-political investment.